AL-FEC for Improved Mobile Reception of MPEG-2 DVB-T Transport Streams. (7th September 2009) - Gozálvez, David; Gómez-Barquero, David; Stockhammer, Thomas; Luby, Michael
Abstract : We investigate the use of application layer FEC protection in DVB-T (Digital Video Broadcasting-Terrestrial) networks for the provision of mobile services. Mobile reception is characterized by variations of the received signal caused by fast fading and shadowing. DVB-T was originally designed for fixed and portable reception, and generally does not provide enough quality in mobile environments. The link layer protection mechanism MPE-FEC (Multi Protocol Encapsulation-Forward Error Correction) was standardized in DVB-H (Digital Video Broadcasting-Handheld) for the protection of mobile TV services. Although DVB-T itself does not incorporate any link or application layer protection mechanism, AL-FEC (Application layer Forward Error Correction) protection can be introduced in DVB-T in a backwards compatible way. By means of AL-FEC, it is possible to improve the robustness of DVB-T services for the provision of mobile TV. In this paper, we explain the concept of AL-FEC protection in DVB-T and evaluate its performance by means of laboratory measurements and dynamic simulations with shadowing. We study different configurations of AL-FEC and compare its performance with MPE-FEC. In this paper, we discuss some implementation aspects of AL-FEC in real scenarios and propose an implementation based on Raptor codes and hash sequences. We also present results obtained by a first AL-FEC prototype for DVB-T that demonstrates the feasibility of the approach.